Resource Extraction Developmentalism and the Coal Industry Across the Indonesian Archipelago: to the Benefits of Whom? - Jasmine Savitri (WIMAYA, 2022)
Over the years, the government of Indonesia has relied on different natural resources as its income generator. Although oil is still a main contributor, coal has increased significance that the business is growing rapidly. The government of Indonesia even promoted the industry’s expansion through legal means, The 2020 Amendment of Coal and Mineral Mining Law, which lays the foundation of its down streaming. Despite domestic and international outcry for a more aggressive response towards climate crisis, Indonesia’s coal industry is ever flourishing and yet to face its end. Nonetheless, local and marginalized communities have to bear its various negative consequences and the environment is facing even further degradation, while a few elites live off of the benefits.